Systematic review of cardiovascular neurocristopathy—contemporary insights and future perspectives - Soliman, Osama; Acharya, Yogesh; Gilard, Martine; Duffy, Garry; Wijns, William; Kannan, Venkatesh; Sultan, Sherif (Frontiers in Cardiovascular Medicine, 2024)
Cardiac neural crest (CNC) cells, originating from the dorsal neural tube, are pivotal architects of the cardio-neuro-vascular domain. They orchestrate the embryogenesis of critical structures such as the thoracic aorta, innominate artery, left common carotid, left subclavian, and cardiac septae. However, disruptions in CNC signalling pathways during cardiovascular development can lead to anomalous migration and differentiation, ultimately culminating in fatal cardiovascular abnormalities. These embryological aortopathies within this region are collectively termed ‘cardiovascular neurocristopathy’ and are associated with a spectrum of cardiac and cerebral-vascular consequences. Specific phenotypes of thoracic aortic diseases linked to CNC disruption can prove fatal if not addressed promptly. Remarkably, while the scientific community compiled a comprehensive inventory of neural crest derivatives by the early 1980s, our understanding of the CNC's role in various cardiovascular disease processes remains relatively underexplored. This review delves into the differentiation of neural crest cells, specifically the CNC cells, and embarks on an exploration of the diverse facets of non-syndromic cardiovascular neurocristopathies.